1981
DOI: 10.1113/jphysiol.1981.sp013798
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins alter the relationship between gastric hydrogen ion concentration and flow: evidence for stimulation of non‐parietal secretion in the cat

Abstract: SUMMARY1. The effect of i.v. administration of prostaglandin (PG) E2 (10-40 jug kg-' h-'), 16,16-dimethyl PGE2 (0-1-0-5 jag kg-h-'), PGE, (16)(17)(18)(19)(20) jg kg-h-1), PGA, (5-11 #ug kg-' h-') and PGF2a (40 , 3. At the dose tested, PGF2a had little effect on acid output, and did not alter the relationship between [H+] and gastric flow.4. There is a linear relationship between acid output and gastric flow and this relationship is similar during stimulation of gastric secretion by pentagastrin, histamine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Studies in vivo have shown that prostaglandins stimulate non-parietal secretion from mammalian stomach (rat: Bolton, Palmer & Cohen, 1978; dog: cat: Gascoigne & Hirst, 1981), and that this secretion consists principally of Na+ and Clions with smaller amounts of K+ and HC03-(dog: Miller, Henagan, Watkins & Loy, 1983;cat: Smeaton & Hirst, 1984;rat: Bunce, 1985). Studies on non-parietal secretion in mammalian isolated tissues have shown that 16,16-dimethyl-prostaglandin E2 stimulates bicarbonate secretion in rabbit gastric mucosa (Rees, Gibbons & Turnberg, 1983), although no such secretion was observed in dog gastric mucosa (Kuo, Miller & Shanbour, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vivo have shown that prostaglandins stimulate non-parietal secretion from mammalian stomach (rat: Bolton, Palmer & Cohen, 1978; dog: cat: Gascoigne & Hirst, 1981), and that this secretion consists principally of Na+ and Clions with smaller amounts of K+ and HC03-(dog: Miller, Henagan, Watkins & Loy, 1983;cat: Smeaton & Hirst, 1984;rat: Bunce, 1985). Studies on non-parietal secretion in mammalian isolated tissues have shown that 16,16-dimethyl-prostaglandin E2 stimulates bicarbonate secretion in rabbit gastric mucosa (Rees, Gibbons & Turnberg, 1983), although no such secretion was observed in dog gastric mucosa (Kuo, Miller & Shanbour, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of prostaglandins is likely to be multifactorial (Miller, 1983). Prostaglandins stimulate the non-parietal component of gastric secretion rich in NaCl (Gascoigne & Hirst, 1981;Smeaton & Hirst, 1984;Bunce, 1985). Although there is one report that prostaglandin increased the net absorption of Na+ in the dog gastric mucosa (Chaudhury & Jacobson, 1978), in both amphibian (Schiessel, Matthews, Barzilai, Merhav & Silen, 1980) and guinea-pig gastric mucosa (Bunce & Spraggs, 1988) there is good evidence for prostaglandin stimulation of electrogenic Cl-secretion.…”
Section: Introductionmentioning
confidence: 99%